Glial activation in the early stages of brain metastasis: TSPO as a diagnostic biomarker. - O'Brien, E; Kersemans, V; Tredwell, M; Checa, B; Serres, S; Soto, MS; Gouverneur, V; Leppert, D; Anthony, D; Sibson, N (Society of Nuclear Medicine Inc., 2014)
UNLABELLED: Metastatic spread of cancer cells to the brain is associated with high mortality, primarily because current diagnostic tools identify only well-advanced metastases. Brain metastases have been shown to induce a robust glial response, including both astrocyte and microglial activation. On the basis of these findings, we hypothesized that this stromal response may provide a sensitive biomarker of tumor burden, in particular through the use of SPECT/PET imaging agents targeting the translocator protein (TSPO) that is upregulated on activated glia. Our goals, therefore, were first to determine the spatial and temporal profile of glial activation during early metastasis growth in vivo and second to assess the potential of the radiolabeled TSPO ligand (123)I-DPA-713 for early detection of brain metastases. METHODS: Metastatic mouse mammary carcinoma 4T1-green fluorescent protein cells were injected either intracerebrally or intracardially into female BALB/c mice to induce brain metastases. Astrocyte and microglial activation was assessed immunohistochemically over a 28-d period, together with immunofluorescence detection of TSPO upregulation. Subsequently, SPECT imaging and autoradiography were used to determine in vivo binding of (123)I-DPA-713 at metastatic sites. RESULTS: Dynamic astrocyte and microglial activation was evident throughout the early stages of tumor growth, with the extent of astrocyte activation correlating significantly with tumor size (P < 0.0001). Microglial activation appeared to increase more rapidly than astrocyte activation at the earlier time points, but by later time points the extent of activation was comparable between the glial cell types. Upregulation of TSPO expression was found on both glial populations. Both autoradiographic and in vivo SPECT data showed strong positive binding of (123)I-DPA-713 in the intracerebrally induced model of brain metastasis, which was significantly greater than that observed in controls (P < 0.05). (123)I-DPA-713 binding was also evident autoradiographically in the intracardially induced model of brain metastasis but with lower sensitivity because of smaller tumor size (∼ 100-μm diameter vs. ∼ 600-μm diameter in the intracerebral model). CONCLUSION: These data suggest that the glial response to brain metastasis may provide a sensitive biomarker of tumor burden, with a tumor detection threshold lying between 100 and 600 μm in diameter. This approach could enable substantially earlier detection of brain metastases than the current clinical approach of gadolinium-enhanced MR imaging.